The Community Master Plan of Ban Hoeybong, Pongtum Sub-District, Chaiprakarn District, Chiang Mai Province - Rithu, Khanchai; Somboonchai, Ratchanon; Nakayan, Phanit; Narata, Poramin (Saengtham College Journal, 2025)
The purposes of this research and development were: 1) to study the basic social, economic, resource and environmental contexts of Ban Huaybong, Chai Prakan, Chiang Mai. 2) to study the problems and needs of the community in various areas of development. 3) to prepare a community master plan for Ban Huaybong in accordance with the real needs and context of the Ban Huaybong Catholic community. Using a representative household population of 136 people and a sample of 30 key informants, purposive sampling was used. Questionnaires and focus groups were used as data collection tools. Data were analyzed using mean, percentage, content analysis and inductive summary analysis. The research findings were as follows: Ban Huaybong is an ethnic community of Pgaz K’nyau. The village was established 65 years ago. Located on a flat area of foothill plain. It is a Catholic community. Most of the population is engaged in agriculture and general labor. The analysis of the community found that the eternal factors were the community strengths with a strong society structure. It possessed potential readiness in both geography and social conditions according to the concept of sustainable geo-social development. They had outstanding social capital, both identity and uniqueness in Chaiprakarn district area and capital in natural resources and the environment, especially water resources coming from the upstream forest which was an abundant natural water source for use in the community. In the aspect of problems and needs of the community found that the disadvantage of the community was the leaders and villagers lacked knowledge and understanding in methods and management approaches in applying it with the strengths in the community causing inability to further develop or link with existing partners, networks, government agencies and private sectors; also, the problems in the management of water sources for consumption, family drug dependence and debt problems arising from investments in the agricultural activities. In preparing the community master plan, the villagers realized the changes in society and the problems that occurred in the community. The community had 4 goals in developing and setting strategies as follows: Strategy 1. Restoration of beliefs, continuation, preservation, and further development of culture and good community traditions. Strategy 2. Social and economic development within the community to have a good quality life. Strategy 3. Maintaining and utilizing the community’s natural resources and environment in a sustainable and balanced way. Strategy 4. Effective community management.